2013
DOI: 10.1016/j.cellsig.2012.09.009
|View full text |Cite
|
Sign up to set email alerts
|

PKB-mediated PHF20 phosphorylation on Ser291 is required for p53 function in DNA damage

Abstract: Publisher rights This is the author's version of a work that was accepted for publication in Cellular Signalling. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive version was subsequently published in Cellular Signalling, VOL25, ISSUE1, 01/2013General rights Copyright for the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Recent reports indicated that PHF20 was phosphorylated at Ser291 and Ser265 by Akt/PKB 29,30 . Here, we further assessed whether the phosphorylation status of PHF20 is functionally involved in its effect on p65 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports indicated that PHF20 was phosphorylated at Ser291 and Ser265 by Akt/PKB 29,30 . Here, we further assessed whether the phosphorylation status of PHF20 is functionally involved in its effect on p65 phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…The activity of Runx2 is precisely regulated by other interacting proteins 25 . PHF20 can also interact with other proteins to control cellular activity along with methylation and acetylation processes of proteins 19 , 26 . For example, PHF20 can function as an effector of p53 methylation to stabilize and activate the protein 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Reporter constructs containing mouse Osteocalcin gene 2 promoters-Luciferase (Og2-Luc) construct was kindly provided by Dr. Renny T Franceschi (University of Michigan School of Dentistry, Ann Arbor, MI, USA). Full length PHF20 (Flag-PHF20) and adenovirus PHF20 (Ad-PHF20) were previously described 26 .…”
Section: Methodsmentioning
confidence: 99%
“…PHF20 has since been identified as a histone code reader that specifically recognizes the dimethylation of H3K4, H3K9, H4K20, and H4K79 (Adams-Cioaba et al, 2012; Kim et al, 2006). Recent studies show that it also regulates p53 protein at both the transcriptional and posttranscriptional levels in response to DNA damage (Li et al, 2012b; Park et al, 2012). Mice with PHF20 ablation die shortly after birth (Badeaux et al, 2012).…”
Section: Discussionmentioning
confidence: 99%